A Study on Utilization of Waste Materials and Eco-Friendly Construction Materials to Make Green Concrete (International Journal of Innovative Research in Computer Science & Technology, 2022)
Tyre is rubber member that provides cushion  against the shocks and support load. Tyre is waste material  which cause many environmental effects in all the parts of  the world representing very serious threat to ecology. One of  the possible solutions for the use of scrap tyre rubber is to  incorporate it into concrete, to replace some of the natural  aggregate. Waste rubber tyre is one of the significant  environmental problems worldwide. The waste tyres rubber  is not easily biodegradable even after long-period of landfill  treatment. The land filing of waste tyre creates soil and water  pollution, because the waste tyre rubber holds toxic and  soluble components. Burning of tyres results in serious fire  hazards and produce many harmful gases. Due to rapid  increase in waste tyres many countries banned the disposal  of waste rubber tyre in landfills. Hence, the civil engineering  use the waste tyres in projects .Rubber tyre c are a waste  material that is ideal for use in concrete applications. This has  an additional advantage of saving in natural aggregates used  in production of concrete which are becoming increasingly  scarce. In this essence, our present study aims to use of waste  rubber tyre as partial replacements of rubber (10,20,30%)  with coarse aggregate. Ordinary Portland cement (OPC) and  natural aggregates, which are the key constitutes of concrete,  are suggested to recycled or substituted in order to address  the sustainability concern. Here by product have been  targeted to reduce carbon footprints.  Fly ash is a by-product at thermal power stations. An  industrial by-product may be inferior to traditional materials  used construction applications, but, the lower cost of these  inferior materials make it an attractive alternative if adequate  performance can be achieved. The use of fly ash is accepted  worldwide due to saving in cement, consuming industrial  waste and making durable or workable materials, especially  due to improvement in the quality fly ash products.
Keywords: Green Concrete; Flyash; Tyres; Recycled Coarse aggregate; Fine aggregate; Cement and Software 2007